Pharmacological profiling of sigma 1 receptor ligands by novel receptor homomer assays. (1st May 2018) - Yano, Hideaki; Bonifazi, Alessandro; Xu, Min; Guthrie, Daryl A.; Schneck, Stephanie N.; Abramyan, Ara M.; Fant, Andrew D.; Hong, W. Conrad; Newman, Amy H.; Shi, Lei
Abstract: The sigma 1 receptor (σ1 R) is a structurally unique transmembrane protein that functions as a molecular chaperone in the endoplasmic reticulum (ER), and has been implicated in cancer, neuropathic pain, and psychostimulant abuse. Despite physiological and pharmacological significance, mechanistic underpinnings of structure-function relationships of σ1 R are poorly understood, and molecular interactions of selective ligands with σ1 R have not been elucidated. The recent crystallographic determination of σ1 R as a homo-trimer provides the foundation for mechanistic elucidation at the molecular level. Here we report novel bioluminescence resonance energy transfer (BRET) assays that enable analyses of ligand-induced multimerization of σ1 R and its interaction with BiP. Haloperidol, PD144418, and 4-PPBP enhanced σ1 R homomer BRET signals in a dose dependent manner, suggesting their significant effects in stabilizing σ1 R multimerization, whereas (+)-pentazocine and several other ligands do not. In non-denaturing gels, (+)-pentazocine significantly decreased whereas haloperidol increased the fraction of σ1 R multimers, consistent with the results from the homomer BRET assay. Further, BRET assays examining heteromeric σ1 R-BiP interaction revealed that (+)-pentazocine and haloperidol induced opposite trends of signals. From molecular modeling and simulations of σ1 R in complex with the tested ligands, we identified initial clues that may lead to the differed responses of σ1 R upon binding of structurally diverse ligands. By combining multiple in vitro pharmacological and in silico molecular biophysical methods, we propose a novel integrative approach to analyze σ1 R-ligand binding and its impact on interaction of σ1 R with client proteins. Highlights: Both our experimental and computational results support the topology revealed by the crystal structures of σ1 R. Novel BRET assays are capable of examining σ1 R homomeric and σ1 R-BiP heteromeric interactions upon ligand binding. Our findings shed light on the ligand-induced conformational changes of σ1 R.